Računsko reševanje inverznega problema oblikovanja nadzvočne šobe - Martinis, Vinko (Strojniški vestnik, 2002)
The numerical design of a nozzle is sensitive to stability in the region of supersonic flow. In the numerical algorithm presented in this paper the instability is avoided by the introduction of an analytically set pressure distribution on the axis of the axisymmetrical supersonic nozzle. The flow parameters of the inverse designed nozzle are checked by the application code FLUENT and they show a regular distribution on cross-sections along the nozzle.
Keywords: šobe nadzvočne; oblikovanje šob; modeli računski; problemi inverzni; nadzvočna šoba; stabilnost; matematični modeli